Fiber-optic sensors for real-time temperature monitoring in minimally invasive thermo-therapies - Sovetov, Sultan (Nazarbayev University School of Engineering and Digital Sciences, 2018)
There are various procedures for the tumor removal process, which include surgical procedures and thermal ablation processes. The surgical method is considered as the traditional one; however, the thermal ablation processes are conducted as well. These thermal ablation processes require temperature change monitoring of the area of the tissue, where the heat is applied. In this work, it is suggested to use fiber-optic sensors for temperature change monitoring in minimally invasive thermo-therapies for cancer care. The comparison of fiber-optic sensors, based on the 5-element FBG array, the CFBG, and the OBR, all of which are operating in real-time and suggested to be used for the temperature change monitoring in minimally invasive thermo-therapies for cancer care was provided in this work. The following criteria was used to compare these temperature sensing technologies: spatial resolution, temperature sensing range, hardware setup, time required for temperature change reconstruction and cost. There were experiments conducted in both the laboratory and in the clinical settings. Also, various recommendations and improvements for future experiments were provided as well. Considering the minimal invasiveness, low-cost and operation in real-time, all of the previously mentioned fiber-optic sensors could be used for the given application; however, the CFBG sensor is suggested to be the most suitable one compared to its alternatives, which are the 5-element FBG array and the OBR-based sensors.